Política educacional inclusiva e formação docente - Freitas, Flaviane Pelloso Molina; Schneckenberg, Marisa; de Oliveira, Jáima Pinheiro [UNESP]; Freitas, Carlos Cesar Garcia (My University, 2016)
This study focuses on the analysis of national educational inclusive policy and teacher formation resulting there from. For this, was realized a descriptive analysis of documents by means of notices of competitions for teaching in Paraná found in the years 2003, 2004, 2007 and 2013, having based the authors Cruz (2008), Feldmann (2009) Glat (2007) McCulloch (2012), Mendes (2006), Michels (2006), among others. It can be seen that despite the existence of a policy proposal of national and state inclusive education in the state of Paraná training and inclusive knowledge remain the responsibility of the teacher of special education mode, showing that in the last decade have not yet advanced to a break the segregation of special education towards inclusive education.
Educational inclusive policy and formation teachers
Keywords: Educational policy; Inclusion; Teacher formation